Developing an Entrepreneurship Program (Texas Journal of Multidisciplinary Studies, 2022)
This study was developed to create an entrepreneurship program for those who are willing, interested, with initiatives and the drives to enhance their quality of life, specifically in times of critical situations like pandemic. The author used a qualitative type of research applying the grounded theory among the 25 participants from different walks of life. The study came out that in order to establish a business the following steps must be observed and strictly followed. These steps in developing an Entrepreneurial Activity are the Know thyself, Create a distinct market niche, Test thy new business idea and Clarify thy vision and mission